2007
DOI: 10.1016/j.neuropsychologia.2007.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Within-person trial-to-trial variability precedes and predicts cognitive decline in old and very old age: Longitudinal data from the Berlin Aging Study

Abstract: Neurocomputational modeling and empirical evidence suggest that losses in neuronal signaling fidelity cause senescent changes in behavior. We applied structural equation modeling to five-occasion 13-year longitudinal data from the Berlin Aging Study (n = 447; age range at t1 = 70-102 years) to test whether trial-to-trial reaction time variability in perceptual speed (identical pictures) antecedes and signals longitudinal decline in levels of performance on perceptual speed (digit letter and identical pictures)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
166
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(190 citation statements)
references
References 80 publications
18
166
1
1
Order By: Relevance
“…Several approaches exist for calculating intraindividual trial-to-trial variability, including intraindividual SD and intraindividual coefficient of variation (SD/M) (Lövden et al, 2007). In the present study, sdRT based on correct congruent and correct incongruent trials was used, as this allowed us to test the effects of IIV both with and without covarying for mRT.…”
Section: Methodsmentioning
confidence: 99%
“…Several approaches exist for calculating intraindividual trial-to-trial variability, including intraindividual SD and intraindividual coefficient of variation (SD/M) (Lövden et al, 2007). In the present study, sdRT based on correct congruent and correct incongruent trials was used, as this allowed us to test the effects of IIV both with and without covarying for mRT.…”
Section: Methodsmentioning
confidence: 99%
“…We tested for linear effects of mRT on FA, RD, AD, and MD with general linear models (GLM) while regressing out the effects of sex and age, and we tested for effects of sdRT on the four DTI parameters regressing out sex, age, and mRT. The research community has not established a standard for calculating intraindividual trial-to-trial variability, and several approaches exist, including intraindividual SD and intraindividual coefficient of variation (Lövdén et al, 2007). In the present study, intraindividual SD was used.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, four studies also reported results for change in IIV over time, and were described in the preceding section (Bielak et al, 2010b;de Frias et al, 2012;Lovden et al, 2007;MacDonald et al, 2003).…”
Section: Associations Between Variability and Outcomementioning
confidence: 99%